Experiences of refugees in public healthcare services a report study on the project presented to - Khanyile, Thamsanqa (My University, 2017)
The city of Johannesburg is one of the largest cities in South Africa and the whole of Africa attracting foreign nationals from across Africa and overseas for numerous reasons ranging from, education, economic or social. With this increase, the number of refugees and migrants flocking into the city puts more pressure on the public health system since most of foreign nationals seek health assistance from public hospitals and clinics (Benatar, 2004). This study sought to explore the subjective experiences of refugees when accessing public health care services and how they are treated by healthcare professionals in South Africa specifically in the area of Johannesburg. With a focus on women and men aged 18 and above who are refugees living in the city of Johannesburg. The study adopted a qualitative approach to explore and understand the subjective experiences of refugees as it is deemed to be more appropriate for this kind of study. The population for this study were refugees from across Africa using public health care services in the area of Johannesburg. Participants were selected using purposeful sampling and snowball techniques. A sample of 6 refugees was selected for the study. Data was collected using interviews which were guided by the use of a semi-structured interview schedule. Thematic analysis was utilized to analyse the data from the interviews. The study results show that refugees encounter negative attitudes from health professionals such as being skipped in the queue to attend South Africans first, some reported being treated in an unjust way. Reasons such as political instability, wars, economic opportunities and searching for better services were reported as the main pull and push factors for refugees.
The Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfilment of the requirements For the degree Bachelor of Social Work